2022
DOI: 10.4236/jbm.2022.1012009
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Insulin Resistance Long Term in the Body and Its Association with the Development of Chronic Diseases

Abstract: Insulin resistance (IR) has become more common in recent years, and it has been related to a number of metabolic disturbances such as obesity, non-alcoholic fatty liver disease (NAFLD), Diabetes mellitus (DM), metabolic syndrome (MetS), cardiovascular disease (CVD), polycystic ovary syndrome (PCOS), and others. IR is defined by a decreased ability of cells to respond to insulin action, as well as hyperglycemia and hyperinsulinemia. There are many factors responsible for the evolution of IR, most notably geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…For example, it has been shown that this massive dietary change was involved in obesity, insulin resistance, type II diabetes, cardiovascular diseases, Alzheimer's disease, hypertension or myopia [2][3][4][5]. Persistent hyperglycemia/hyperinsulinemia, and insulin resistance due to the overconsumption of refined carbohydrates are among the well recognized physiological mechanisms involved in these diseases [1,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that this massive dietary change was involved in obesity, insulin resistance, type II diabetes, cardiovascular diseases, Alzheimer's disease, hypertension or myopia [2][3][4][5]. Persistent hyperglycemia/hyperinsulinemia, and insulin resistance due to the overconsumption of refined carbohydrates are among the well recognized physiological mechanisms involved in these diseases [1,6,7].…”
Section: Introductionmentioning
confidence: 99%